Effect of Academic Supervision and Teachers’ Work Motivation on Learning Quality: A Quantitative Study in Public Elementary Schools - Ahmad Agus Alim; Rasiman Rasiman; Soedjono Soedjono (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This study aims to examine the influence of academic supervision and teachers’ work motivation on the quality of learning in public elementary schools. The research employed a quantitative approach with an ex post facto design. Data were collected through structured questionnaires distributed to teachers and were analyzed using multiple linear regression to determine both partial and simultaneous effects among variables. The findings indicate that academic supervision has a positive and significant effect on learning quality, contributing 48.2% to its variance. Teachers’ work motivation demonstrates a stronger positive and significant effect, with a contribution of 62.3%. Simultaneously, academic supervision and work motivation account for 69.8% of the variance in learning quality, indicating a substantial combined influence. These results suggest that learning quality is shaped by the interaction between external factors, such as systematic and constructive academic supervision conducted by school principals, and internal factors, particularly teachers’ professional motivation. Strengthening collaborative supervision practices alongside fostering teachers’ intrinsic and extrinsic motivation can therefore enhance instructional effectiveness. The study underscores the importance of integrated strategies in improving primary education quality through leadership support and sustained teacher motivation Keywords: academic supervision; teachers’ work motivation; learning quality